Nicotinamide Adenine Dinucleotide Phosphate Oxidase 2 Expression and Effects of Alpha Lipoic Acid on Recovery in a Rat Model of Facial Nerve Injury - Myung Chul Yoo; In Yong Ryu; Jin Woo Choi; Jae Min Lee; Jae Yong Byun; Seung Geun Yeo (Biomedicines, 2022)
Background: NOX2 (nicotinamide adenine dinucleotide phosphate oxidase 2), which is upregulated by a variety of neurodegenerative factors, is neuroprotective and capable of reducing detrimental aspects of pathology following ischemic and traumatic brain injury, as well as in chronic neurodegenerative disorders. The purpose of this study was to investigate NOX2 expression and the degree of functional recovery following different types of facial nerve injury and assess the effects of antioxidant intervention on nerve regeneration. Methods: A total of 40 mature (6-week-old) male Sprague-Dawley (SD) rats were used. After inducing facial injury (compression injury or cutting injury), we randomized rats into four groups: A, crushing injury only; B, crushing injury with alpha lipoic acid (ALA); C, axotomy only; and D, axotomy with ALA. Recovery from facial nerve injury was evaluated 4 and 14 days after injury by performing behavioral assessments (observational scale of vibrissae movement, modified scale of eye closing and blinking reflex) and measuring changes in NOX2 experimental/control ratio in the injured (left, experimental) facial nerve relative to that in the uninjured (right, control) facial nerve. Results: A comparison between groups according to the type of injury showed a higher NOX2 expression ratio in the axotomy group than in the crushing group (p < 0.001). Regardless of injury type, both groups that received an injection of ALA exhibited a trend toward a higher NOX2 expression ratio, although this difference reached statistical significance only in the axotomy group (p < 0.001). In behavioral assessments, overall behavioral test scores were significantly higher in the crushing injury group immediately after the injury compared with that in the axotomy group. Additionally, in behavioral tests conducted 4 days after the crushing injury, the group injected with ALA showed better results than the group without injection of ALA (p = 0.031). Conclusions: Our study showed that NOX2 expression trended higher with facial nerve injury, exhibiting a significant increase with cutting-type injury. Furthermore, intraperitoneally injection with ALA may be an efficient strategy for accelerating peripheral facial nerve recovery after a crushing injury.